1994
DOI: 10.1111/j.1476-5381.1994.tb14889.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of ω‐conotoxin GVIA and tetrodotoxin on vasoconstrictions evoked by electrical stimulation and nicotinic receptor stimulation in canine isolated, perfused splenic arteries

Abstract: 1 The effects of w-conotoxin GVIA (Qo-CgTX) and tetrodotoxin (TTX) on vasoconstrictions induced by acetylcholine (ACh) and nicotine were investigated and compared with those induced by periarterial electrical stimulation in the isolated and perfused canine splenic arteries. 5 Vascular responses to ACh were completely inhibited by 1 pmol hexamethonium. In the preparations treated with 100 nmol nicotine, ACh did not produce any vasoconstriction. However, the NA-induced vasoconstriction was affected by neither he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 36 publications
0
12
1
Order By: Relevance
“…29 TTX is a reversible selective inhibitor of sodium channel conductance, 6,7 which can block nerve conduction, which in turn effects the efficiency of transmitter release. 30,31 We have a hypothesis that the efficacy of TTX in attenuating the severity of acute withdrawal syndrome might be as a result of these effects on peripheral sodium channels. However, although the present results support the finding that TTX can alleviate acute heroin withdrawal syndrome, more preclinical research is required to describe the exact mechanism by which this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…29 TTX is a reversible selective inhibitor of sodium channel conductance, 6,7 which can block nerve conduction, which in turn effects the efficiency of transmitter release. 30,31 We have a hypothesis that the efficacy of TTX in attenuating the severity of acute withdrawal syndrome might be as a result of these effects on peripheral sodium channels. However, although the present results support the finding that TTX can alleviate acute heroin withdrawal syndrome, more preclinical research is required to describe the exact mechanism by which this occurs.…”
Section: Discussionmentioning
confidence: 99%
“…7-10 Ren et al 14,15 have also reported that 30 nmol/L TTX completely inhibits vasoconstrictor responses to periarterial nerve stimulation in canine splenic artery. 7-10 Ren et al 14,15 have also reported that 30 nmol/L TTX completely inhibits vasoconstrictor responses to periarterial nerve stimulation in canine splenic artery.…”
Section: Discussionmentioning
confidence: 99%
“…The depolarization‐induced release of neurotransmitters is dependent upon a prejunctional influx of extra‐cellular calcium ions through voltage‐gated calcium channels (VGCCs) (Mulkey & Zucker, 1991). N‐type VGCCs have been shown to play a key role in triggering neurotransmitter release from sympathetic nerve terminals (Maggi et al ., 1988; De Luca et al ., 1990; Pruneau & Angus, 1990; Fabi et al ., 1993; Ren et al ., 1994; Wright & Angus, 1996). Since adenosine 5′‐triphosphate (ATP) has been proposed as a co‐transmitter with noradrenaline in peripheral sympathetic nervous system (Burnstock, 1972; 1979; 1988), an interesting point raised is whether the release of the two co‐transmitters are subject to parallel modulation by N‐type VGCCs.…”
Section: Introductionmentioning
confidence: 99%